Production potential, economics and energetics of rice (Oryza sativa) genotypes as influenced by varying levels of nitrogen - KUMAR, RAKESH; MISHRA, J S; KUMAR, SANTOSH; HANS, HANSRAJ; BHATT, B P; SRIVASTAVA, A K; SINGH, SUDHANSHU (The Indian Journal of Agricultural Sciences, 2019)
Performance of eight rice (Oryza sativa L.) genotypes (IR 83383–B–B–129–4, IR 83387–B–B–27–4, IR88867– 9–1–1–4, IR88964–24–2–1–4, IR88964–11–2–2–4, IR88966–39–1–4–4, Rajendra Sweta and Rajendra Bhagwati) were evaluated in different levels of nitrogen (N) application, i.e. control, 50% RDN (60 kg N/ha), 100% RDN (120 kg N/ha) and 150% RDN (180 kg N/ha) during the rainy season of 2016–17 in lowland transplanted condition of Patna, Bihar. Significantly higher grain yields (5.19 t/ha) and net returns (` 52260/ha) were recorded with application of 180 kg N/ha. Grain yields and net returns were noted higher with IR 83383–B–B–129–4 (4.27 t/ha and ` 38181/ ha). Carbohydrate equivalent yield (4.06 t/ha) and carbon output (6.42 t CE/ha) were also higher with 150% RDN. IR83383–B–B–129–4 had significantly higher carbohydrate equivalent yield (3.34 t/ha) and carbon output (5.23 t CE/ ha). Gross energy output, net energy return, energy use efficiency, energy profitability, energy productivity, energy intensity in economic terms and energy output efficiency were markedly higher with 180 kg N/ha. These attributes were higher with IR83383–B–B–129–4 but being on a par with IR83387–B–B–27–4. Therefore, growing of IR 83383–B–B–129–4 along with application of 180 kg N/ha is an ideal approach to achieve the higher productivity, profitability and energetics in lowland transplanted condition of Bihar.